Identificando as barreiras ao consumo verde - Pivetta, Natália Pavanelo (2019)
As the transformations that the planet has been suffering increasingly affect the population, it is noticed that a new concept of global consciousness has been emerging. Given this, it is perceived that consumers are increasingly concerned about environmental problems, as well as whether sustainability is embedded in the organizational environment. Aware of this requirement, many companies see consumer behavior towards sustainability as a way to get closer to their customers and meet their expectations, using environmental strategies to strengthen the image of their organizations in the consumer market . However, even with the adaptation of many companies to this trend and the concern expressed by consumers, the literature and practice show that the purchase of these pro-environmental products and services does not show the expected regularity. In this sense, it becomes necessary to know the reasons that make it difficult for consumers to buy green products, ie the barriers that these consumers face. Such knowledge will allow the direction of new strategies, as well as future advances for both theory and practice. In this perspective, the main objective of this study was to identify and analyze the barriers to green consumption faced by Brazilian consumers. In order to achieve the objectives, the study was analyzed from a descriptive perspective with a quantitative approach. For this, a survey of the type survey was carried out through the adaptation and replication of the research instrument on the barriers to green consumption developed by the authors Gleim et al. (2013). This questionnaire was applied to the students of the Administration courses of the South region of Brazil through e-mails. At the end of the data collection, 450 questionnaires were obtained that were considered valid for the analysis. The main results showed that: (1) the profile of the sample investigated is composed mostly of young people, women, with average income between two and six minimum wages, single (a), who have a bachelor's degree in Administration in the most varied semesters, they live with their parents and live in houses; in addition, they do not usually consume green products and those consumers who do have a very low frequency of consumption; (2) the exploratory factorial analysis found the need to eliminate three questions from the research instrument, as well as reduce the total number of factors to thirteen; (3) the univariate analysis allowed to verify that the main barriers faced by the investigated sample are the lack of knowledge and the low availability of these products, in addition, similarities were identified in the results found with other studies in the literature, such as the findings of Gleim et al. (2013) and Ferraz et al. (2013); (4) the bivariate analysis showed 67 significant associations, being verified that most of the constructs are interconnected with each other. From the results, it was identified as one of the limitations of the dissertation the fact that the results refer only to the reality of the sample investigated. As suggestions for future research, the possibility of expanding research at national level with different publics, as well as the use of other methodological approaches, should be highlighted.